P3.186 Neisseria gonorrhoeae antimicrobial resistance surveillance in johannesburg, south africa. (8th July 2017) - Kularatne, Ranmini; Maseko, Venessa; Gumede, Lindy; Radebe, Frans; Kufa-Chakezha, Tendesayi
Abstract : Introduction: Gonorrhoea is the predominant cause of symptomatic male urethritis in South Africa. Neisseria gonorrhoeae has displayed an alarming propensity to acquire resistance to all sequential first-line antimicrobial agents used over the years. The National Institute for Communicable Diseases has co-ordinated STI microbiological surveillance since 2005 in order to validate existing national syndromic management guidelines. We describe Neisseria gonorrhoeae antimicrobial resistance patterns and trends from Johannesburg surveillance, spanning a period of eight years from 2008 to 2015. Methods: Neisseria gonorrhoeae was cultured from swab specimens of genital discharge (endocervical and endourethral) from consenting adult patients presenting to a community-based primary healthcare facility in Johannesburg. The minimum inhibitory concentrations (MICs) of antimcrobials were determined using Etest (cefixime, ceftriaxone, ciprofloxacin) or agar dilution (azithromycin, penicillin, tetracycline). Clinical Laboratory Standards Institute (CLSI) criteria, where applicable, were used for interpretation of results. Descriptive statistics and likelihood-ratio tests in STATA 14 were used for data analysis. Results: A total of 2, 112 Neisseria gonorrhoeae isolates were tested for susceptibility to the extended-spectrum cephalosporins (ESCs) and ciprofloxacin. A proportion of these were tested for susceptibility to penicillin, tetracycline and azithromycin. Between 2011 and 2015, the prevalence of high-level resistance increased from 31% to 57% for penicillin (p=0.009) and 73% to 91% for tetracycline (p=0.009). Between 2008 and 2015, the prevalence of high-level ciprofloxacin resistance rose exponentially from 24% to 67% (p<0.001). Decreased susceptibility (DS) to cefixime was not observed; however one isolate from 2013 exhibited DS to ceftriaxone. Trend analysis revealed MIC creep for cefixime. Elevated azithromycin MICs of >0.5 µg/ml were identified only in 2015 (5/125; 4%). Conclusion: Neisseria gonorrhoeae resistance trends for Johannesburg reveal that high-prevalence resistance to penicillin, tetracycline and ciprofloxacin obviates their use for STI syndromic management. The prevalence of resistance to ESCs is <1% and to azithromycin <5%, validating their continued use in dual therapy. However, it is essential that ESC and azithromycin susceptibility trends are monitored to detect emerging resistance timeously.